O brincar e a clínica fonoaudiológica - Pollonio, Claudia Fernanda (2005)
This research has the main objective to investigate the playing statute in Speech Language (SLP). First of all, for the execution I did the option to guide this work in those areas that put playing as the focal point of its problamatic, like psychology and psychoanalysis, fields which were the support to stabblish relation between SLP and playing. I try to make clear as playing has been dealt by SLP and not omitting that different influences theorical methodologic deal to divergent ways of playing the clinical scene. By reason of those influences that I structured a proposal inside SLP that could clarify the statute of playing in that area. The references about methodological theory made use in one side of psychoanalysis, concerning a private working in practice that gives the subject while unconscious and captured by symbolic order and in the other side, from linguistic point of view, based in those discussion that the process of language acquirement for children, it is indeed of the stabblished relations with the Language while the other one and in the notes that it is by speech that rises a child, being alienated to the other one . So, the statute of playing was remeasured inside a structural clinic framework that contemplate the inspirations from both areas. I belive that it is possible to redefiny a statute in playing SLP: the assignament can be a technical instrument that the speech pathologist deals to children therapeutic, whose aim to be reached by therapist is to accomplish the discursive linguistic clinical method